The access to injustice and legal vulnerability based on sex - Contreras Ugarte, Jesús Víctor Alfredo (2020)
The discrimination or vexation of rights suffered by a given person cannot and should never be corrected by causing other discrimination or vexation equal to or worse than that which is intended to be tackled, and even less so against the other who is supposed to remain, at present, the same historical discriminator and vexatious person who is accused. This article will analyse why accepting a kind of exchange of one form of discrimination for another is a contradiction and a recklessness that, in the world of rights, is irrefutably unacceptable.